Automation and its Impact on Productivity and Workers - Ulrich Jürgens (Weizenbaum Journal of the Digital Society)
This article explores the historical development and impact of automation in the automotive industry, focusing on the production systems of Ford, Toyota, and Volkswagen, and addresses two key research questions: How has automation evolved over time? What are its effects on productivity and labor? Drawing on company archives, empirical fieldwork, and the existing literature, the study uses a wcase study approach. The findings reveal that automation progressed in uneven, layered trajectories rather than through disruptive leaps. While machining, press, and paint shops have become highly automated, final assembly remains largely manual. Automation’s influence on productivity has declined over time, with product complexity and shorter model cycles emerging as constraints. Employment effects are nuanced, and shaped by automation, outsourcing, and customization trends. Ultimately, the study cautions against deterministic views of technological change and highlights the persistent role of organizational and institutional factors. The transition to electric vehicles may trigger further automation – but not necessarily through disruptive technologies alone.